The relative controls of temperature and soil moisture on the start of carbon flux phenology and net ecosystem production in two alpine meadows on the Qinghai-Tibetan Plateau. (13th February 2020) - Chai, Xi; Shi, Peili; Song, Minghua; Zong, Ning; He, Yongtao; Li, Yingnian; Zhang, Xianzhou; Liu, Yanjiao
Abstract: Aims: Variations in vegetation spring phenology are widely attributed to temperature in temperate and cold regions. However, temperature effect on phenology remains elusive in cold and arid/semiarid ecosystems because soil water condition also plays an important role in mediating phenology. Methods: We used growing degree day (GDD) model and growing season index (GSI) model, coupling minimum temperature ( T min ) with soil moisture (SM) to explore the influence of heat requirement and hydroclimatic interaction on the start of carbon uptake period (SCUP) and net ecosystem productivity (NEP) in two alpine meadows with different precipitation regimes on the Qinghai-Tibet Plateau (QTP). One is the water-limited alpine steppe-meadow, and the other is the temperature-limited alpine shrub-meadow. Important Findings: We observed two clear patterns linking GDD and GSI to SCUP: SCUP was similarly sensitive to variations in preseason GDD and GSI in the humid alpine shrub-meadow, while SCUP was more sensitive to the variability in preseason GSI than GDD in the semiarid alpine steppe-meadow. The divergent patterns indicated a balance of the limiting climatic factors between temperature and water availability. In the humid meadow, higher temperature sensitivity of SCUP could maximize thermal benefit without drought stress, as evidenced by the stronger linear correlation coefficient ( R 2 ) and Akaike's information criterion (AIC) between observed SCUPs and those of simulated by GDD model. However, greater water sensitivity of SCUP could maximize the benefit of water in semiarid steppe-meadow, which is indicated by the stronger R 2 and AIC between observed SCUPs and those of simulated by GSI model. Additionally, although SCUPs were determined by GDD in the alpine shrub-meadow ecosystem, NEP was both controlled by accumulative GSI in two alpine meadows. Our study highlights the impacts of hydroclimatic interaction on spring carbon flux phenology and vegetation productivity in the humid and semiarid alpine ecosystems. The results also suggest that water, together with temperature should be included in the models of phenology and carbon budget for alpine ecosystems in semiarid regions. These ﬁndings have important implications for improving vegetation phenology models, thus advancing our understanding of the interplay between vegetation phenology, productivity and climate change in future.